2014
DOI: 10.1239/aap/1396360100
|View full text |Cite
|
Sign up to set email alerts
|

On Comparison of Clustering Properties of Point Processes

Abstract: In this paper, we propose a new comparison tool for spatial homogeneity of point processes, based on the joint examination of void probabilities and factorial moment measures. We prove that determinantal and permanental processes, as well as, more generally, negatively and positively associated point processes are comparable in this sense to the Poisson point process of the same mean measure. We provide some motivating results on percolation and coverage processes, and preview further ones on other stochastic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 33 publications
2
61
0
Order By: Relevance
“…From the definition of the log-concave ordering < lc in [46] it follows that η K (B) < lc Y , where Y is described above, which in turn implies that η K (B) < cx Y , see Theorem 1 in [46]. The above corollary for the case of jointly observable sets and X = R d was observed by Blaszczyszyn and Yogeshwaran in [4], Proposition 5.3, using a different argument. for any t, a > 0, and the upper bounds can be replaced by the values taken from the dominating in < dcx process.…”
Section: < DCX Comparisons For Mixed Sampled and Determinantal Point mentioning
confidence: 77%
See 1 more Smart Citation
“…From the definition of the log-concave ordering < lc in [46] it follows that η K (B) < lc Y , where Y is described above, which in turn implies that η K (B) < cx Y , see Theorem 1 in [46]. The above corollary for the case of jointly observable sets and X = R d was observed by Blaszczyszyn and Yogeshwaran in [4], Proposition 5.3, using a different argument. for any t, a > 0, and the upper bounds can be replaced by the values taken from the dominating in < dcx process.…”
Section: < DCX Comparisons For Mixed Sampled and Determinantal Point mentioning
confidence: 77%
“…Directly from the definition of sNA we conclude that P(η(B) = 0), η(B ′ ) = 0) ≤ P(η(B) = 0)P(η(B ′ ) = 0). Now, from Proposition 3.1 in [4] we get that P(η(B) = 0) ≤ exp( −Eη(B) 1 (B)). Then…”
Section: Na and Dependence Orderings For Point Processesmentioning
confidence: 90%
“…The critical node density of a clustered point process is not the same as the critical node density of the homogeneous Poisson point process for percolation. More detailed study on the percolation of a clustered point process can be found in [21]. Fig.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…To quantify the impact of clustering properties among point processes, the directionally convex order on point processes [24] and the properties of positive and negative association [25], [26] have been proposed. This was for instance used to compare certain point processes with the Poisson point process [27].…”
Section: A Motivationmentioning
confidence: 99%